2005
DOI: 10.1111/j.1540-6261.2005.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Finance and the Business Cycle: International, Inter‐Industry Evidence

Abstract: By considering yearly production growth rates for several manufacturing industries in more than 100 countries during (roughly) the last 40 years, we show that industries that are more dependent on external finance are hit harder during recessions. The observed difference in the behavior of industries is larger when financial frictions are thought to be more prevalent, linking the result directly to the financial mechanism hypothesis. In particular, more dependent industries are more strongly affected in recess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
299
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 390 publications
(316 citation statements)
references
References 47 publications
(64 reference statements)
16
299
0
1
Order By: Relevance
“…Besides, banking crises in emerging markets are often accompanied by currency crises (Beck et al, 2003). (Seyfried and Ewing, 2001), and growth (Grier and Grier, 2006); e) raising interest rates (UNCTAD, 2006) with negative growth effects (Nickell and Nicolitsas, 1999); f) damaging firm balance sheets and net worth (Bernanke and Gertler, 1990;Braun and Larrain, 2005); and g) discouraging international trade by raising transaction risk (Grier and Smallwood, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, banking crises in emerging markets are often accompanied by currency crises (Beck et al, 2003). (Seyfried and Ewing, 2001), and growth (Grier and Grier, 2006); e) raising interest rates (UNCTAD, 2006) with negative growth effects (Nickell and Nicolitsas, 1999); f) damaging firm balance sheets and net worth (Bernanke and Gertler, 1990;Braun and Larrain, 2005); and g) discouraging international trade by raising transaction risk (Grier and Smallwood, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, firms with maturity mismatch problem will suffer from fluctuations in short term interest rates as the monetary authority intervenes to curtail excess volatility, or as the risk premium on external borrowing increases. And third, as the risk premium increases, rising cost of external borrowing will hurt those firms with higher leverage ratios and external finance dependence more through decreasing supply and increasing cost of external finance (Braun and Larrain, 2005). …”
Section: Access To External Creditmentioning
confidence: 99%
“…Regarding earlier episodes, it was found that industries that are more dependent on external finance are hit harder during recessions (a finding corroborated by Braun and Larrain, 2005) and these industries recover disproportionately less during a creditless recovery than those that are more self-financed (a finding of Abiad, Dell'Ariccia and Li, 2011). When bank loans, debt securities and equity are not perfect substitutes, these findings suggest that impaired financial intermediation, and hence limitations in credit supply, was a major reason for past creditless recoveries.…”
Section: Credit Supply and Demandmentioning
confidence: 51%
“…Similarly to Braun and Larrain (2005), Abiad, Dell'Ariccia andLi (2011) andBijsterbosch andDahlhaus (2011), we define the trough of the business cycle as the lowest point of the cyclical component of real GDP identified by the Hodrick-Prescott filter with smoothing parameter 6.25, which is the suggestion of Ravn and Uhlig (2002) for annual data. We only consider those troughs for which the lowest point of the cyclical component is below zero by more than its standard deviation.…”
Section: Definitions Of Business Cycle Trough and Creditless Recoveriesmentioning
confidence: 99%
“…Another possibility is that firms differ in terms of the tangibility of their assets, and protection for less tangible ones is poorer in less developed markets (Braun, 2003;Braun and Larrain, 2005). If this is so, one would expect firms with many intangible assets to have more difficulty in getting external funds, and so to be underrepresented in equity markets.…”
Section: Industry Characteristicsmentioning
confidence: 99%